Effects of ZnCl2 catalyst loading in hydrothermal carbonization of cotton textile waste to produce hydrochars / Muhammad Kasyfil Adha Rosly... [et al.] - Rosly, Muhammad Kasyfil Adha; Wan Kamis, Wan Zuraida; Ali Bashah, Nur Alwani; Isa, Norain; Inderan, Vicinisvarri; Mohd Din, Azam Taufik (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Hydrothermal carbonization (HTC) is a thermochemical process that utilizes biomass as feedstocks to produce hydrochars as solid fuel. Cotton textile wastes (CTW) are abundant; most are landfilled or incinerated, causing environmental pollution. CTW is rich in cellulose, thus suitable as biomass feedstock. HTC at a moderate temperature below 230 °C yields low-value hydrochars with low carbon content; however, an acid catalyst enhances the reaction. In this study, zinc-activated cotton textile waste (Zn-CTW) was synthesized via incipient wetness impregnation and used as a catalyst in hydrothermal carbonization to produce hydrochars. The reactions were conducted in a batch reactor at a temperature of 200 °C for 3 h. The effects of ZnCl2 catalyst loading on CTW were studied. The characteristics of hydrochars in terms of surface morphologies, hydrogen/carbon (H/C) and oxygen/carbon (O/C) ratios and surface functional groups were affected by the ZnCl2 loading on CTW. The results show that the hydrothermal carbonization of Zn-CTW-1.5 obtained hydrochars with the lowest H/C and O/C ratio values of 1.286 and 0.614, respectively. The FTIR analysis indicates stretching vibration of the C-O bond, which are the carboxylic acids and esters formed in the hydrochars. The hydrochars' surface morphologies show irregular and rough surfaces. It is concluded that Zn-CTW has the potential as a heterogeneous catalyst to produce hydrochars via hydrothermal carbonization